ANALISIS KESESUAIAN PENERAPAN SISKEUDES DALAM PENGELOLAAN DANA DESA - Elsa Manora Wongku; Aprina Nugrahesthy Sulistya Hapsari (AkMen JURNAL ILMIAH, 2019)
This study aims to analyze the suitability of the application between the stages of village financial management according to Permendagri No. 20 of 2018 with the stages of village fund management in Karangtengah Village, Tuntang District, Semarang Regency by using the Siskeudes application. This research is a qualitative descriptive study. This type of research data was obtained from primary data that is data obtained from interviews and documentation. Qualitative analysis techniques used are data reduction, data presentation and conclusion drawing. The results and discussion of this study indicate that the stages of Permendagri village financial management No. 20 of 2018 with the stages of village fund management starting from the stages of planning, implementation, administration, reporting and accountability through the Siskeudes application in Karangtengah Village are appropriate and are generally well implemented and running smoothly until now .. However, there are differences in inputting to the National Secretariat and manual components not inputted in the National Secretariat but it does not make the process of village fund management in the National Secretariat and accountability hampered because the National Secretariat also complements the attachments.